In Vivo reconstruction of Human Erythropoiesis with Circulating Mature Human RBCs in Humanized Liver Mistrg Mice - Song, Yuanbin; Shan, Liang; Gbyli, Rana; Liu, Wei; Fu, Xiaoying; Wang, Xiaman; Qin, Ashley; Patel, Amisha; Gao, Yimeng; Tebaldi, Toma; Biancon, Giulia; Urbonas, David; et al. (Blood, 2019)
The murine host has remained a readily available and ethically acceptable model for the study of human diseases and therapeutic testing. Immunodeficient mouse models support engraftment of human hematopoietic stem cells (HSC) but with limitation in efficiency and mature lineage representation. Combined knock-in of several non-crossreactive human cytokines (M-CSF, IL3/GM-CSF, and Thrombopoietin) into the corresponding murine loci in the SRG strain (in short termed “MISTRG”) has enhanced engraftment and maintenance of human HSCs with multi-lineage differentiation (Rongvaux et al. Annu Rev Immunol 2013, Deng et al. Nature 2015, Saito et al. Blood 2016, Theocharides et al. Haematologica 2016). Despite robust HSC engraftment and myelo- and erythropoiesis in bone marrow (BM), all humanized immunodeficient mouse models lack of mature human red blood cells (RBC), platelets, and myeloid cells in peripheral blood (PB) (Rahmig et al. Stem Cell Reports 2016, Yurino et al. Stem Cell Reports 2016, Song et al. Nat Commun 2019). Yet, full maturation and representation of all myeloid lineages in PB is essential to study diseases of the HSC, such as MDS, and of the RBC, such as sickle cell anemia or malaria. With universal absence of a murine adaptive immune system the culprit is likely the murine host's innate immune system. Previous studies have shown that treatment of engrafted mice with liposomal clodronate that abrogates murine (and human) macrophages, with or without cobra venom factor that eliminates complement, can increase mature human circulating RBC, but only transiently and with significant toxicity. We first sought to determine the site of huRBC sequestration and destruction. Intravital imaging after injection of CFSE labelled huRBC identified the murine liver as the major site of RBC destruction. While muRBC rapidly circulate through the liver circulation, huRBC have greatly increased transit times and are sequestered in liver vessels. We hypothesized that humanization of the murine host's liver could potentially alleviate huRBC sequestration and significantly increase circulating huRBC. In previous studies deletion of fumarylacetoacetate hydrolase (Fah) in the Rag-/-Il2rg-/- background has allowed humanization of the liver and served to study diseases such as malaria (Vaughan et al. J Clin Invest 2012). The liver is the site of synthesis of numerous proteins, some of which directly impact hematopoiesis and blood cells, such as complement. We deleted the Fah gene via CRISPR/Cas9 in MISTRG mice and crossed MISTRG-Fah-/- mice to homozygosity (MISTRGFah). MISTRGFah are viable, fertile, and healthy when maintained on drinking water supplemented with 2-(2-nitro-4-trifluoromethylbenzoyl)-1, 3-cyclohexanedione (NTBC), that blocks tyrosine metabolism upstream of Fah and prevents buildup of hepatotoxic metabolites. At 8 weeks of age we implanted MISTRGFah mice with commercially available, adult human hepatocytes (HuHep) via direct injection into the splenic vein, followed by gradual withdrawal of NTBC water. Regulated buildup of intracellular fumarylacetoacetate results in death of murine Fah-/- hepatocytes and regeneration with HuHep with up to 90% repopulation by HuHep (Azuma et al. Nature biotechnology 2007). When plasma human albumin levels reached 2mg/dL, indicative of significant (~80%) HuHep repopulation, we sublethally (80cGy) irradiated HuHepMISTRGFah mice and engrafted each mouse with 105 fetal liver (FL) derived CD34+ cells. 10 weeks post transplantation, mice were analyzed for engraftment and specifically erythroid maturation in PB. HuHepMISTRGFah mice had significantly higher levels of BM and interestingly spleen erythropoiesis and circulating huRBC in PB (Fig.1 a). CD235a+ huRBC in HuHepMISTRGFah mice are enucleated (Hoechst neg) and mature as evident by loss of CD49d (ITGA4) and gain of Band3 staining (Hu et al. Blood 2013) (Fig.1 b). Interestingly, human erythroid cells in MISTRG but not HuHepMISTRGFah mice are coated with murine complement C3 (muC3) (Fig.1 c) suggesting that liver humanization results in loss of muC3 expression. In conclusion, we have generated the first humanized mouse model with fully mature, circulating huRBC when engrafted with human CD34+ stem and progenitor cells. Ongoing studies are testing the applicability of this model to MDS and sickle cell disease. [Display omitted] Flavell:SMOC: Equity Ownership; Zai labs: Consultancy; GSK: Consultancy; Artizan Biosciences: Equity Ownership; Troy: Equity Ownership; Rheos Biomedicines: Equity Ownership.